Antimicrobial prophylaxis does not improve post-surgical outcomes in SIV/SHIV-uninfected or SIV/SHIV-infected macaques (Macaca mulatta and Macaca fascicularis) based on a retrospective analysis. - Cassandra Moats; Kimberly Cook; Kimberly Armantrout; Hugh Crank; Samantha Uttke; Kelly Maher; Rachele M Bochart; George Lawrence; Michael K Axthelm; Jeremy V Smedley (PLoS ONE, 2022)
Surgical antimicrobial prophylaxis is indicated when performing contaminated surgeries, when specific surgical implants are placed, and for prolonged surgical procedures. Unnecessary prophylactic antibiotics are often utilized for macaque surgeries, despite medical and veterinary guidelines. In this study we compared complication rates in macaques receiving peripheral lymph node (PLN) and laparoscopic biopsies, with and without antimicrobial prophylaxis. A majority of animals were SIV or SHIV infected at the time of surgery, so we also compared post-operative complication rates based on infection status. We found no significant difference in PLN biopsy complication rates for animals that received antimicrobial prophylaxis versus those that did not. Animals who underwent laparoscopic procedures and received prophylactic antibiotics had a higher complication rate than those who did not receive them. Complication rates did not differ significantly for SIV/SHIV infected versus uninfected animals for both laparoscopic biopsy procedures and PLN biopsy procedures. SIV/SHIV infected animals that underwent PLN biopsies had no significant difference in complication rates with and without antimicrobial prophylaxis, and SIV/SHIV infected animals receiving prophylactic antibiotics for laparoscopic biopsies had a higher complication rate than those that did not. This study suggests that perioperative prophylactic antibiotics have no role in the management of SIV/SHIV-infected and uninfected macaques undergoing clean, minimally invasive surgeries. Additionally, we recommend eliminating unnecessary antibiotic use in study animals due to their potential confounding impacts on research models and their potential to promote antimicrobial resistance.